Advantages and challenges of fostering cognitive integration through virtual collaborative learning: a qualitative study - Jeanette Ignacio; Hui-Chen Chen; Tanushri Roy (BMC, 2022)
Abstract Background The drastic shift from face-to-face classes to online learning due to the COVID-19 pandemic has enabled educators to ensure the continuity of learning for health professions students in higher education. Collaborative learning, a pedagogy used to facilitate knowledge integration by helping students translate theory from basic sciences to clinical application and practice, has thus been transformed from a face-to-face to a virtual strategy to achieve the learning objectives of a multi-disciplinary and integrated module. Objectives This study aimed to describe and evaluate, through focus group discussions, a virtual collaborative learning activity implemented to assist first year undergraduate nursing students to develop cognitive integration in a module consisting of pathophysiology, pharmacology, and nursing practice. Methods Fourteen first year undergraduate students and four faculty involved in facilitating the virtual collaboration participated in the study. Focus group discussions were conducted to elicit the perceptions of students and staff on the virtual collaborative learning session conducted at the end of the semester. Results Three themes were generated from the thematic analysis of the students' focus group scripts. These were: (1) achieving engagement and interaction, (2) supporting the collaborative process, and (3) considering practical nuances. The three themes were further subdivided into subthemes to highlight noteworthy elements captured during focus group discussions. Three themes also emerged from the focus group discussion scripts of faculty participants: (1) learning to effectively manage, (2) facing engagement constraints, and (3) achieving integration. These themes were further sectioned into salient subthemes. Conclusion The virtual collaborative learning pedagogy is valuable in fostering cognitive integration. However, meticulous planning considering various variables prior to implementation is needed. With better planning directed at addressing the learners' needs and the faculty's capabilities and readiness for online learning pedagogies, and with a strong institutional support to help mitigate the identified constraints of virtual collaborative learning, students and faculty will benefit.